Comparative Analysis of Indonesia and Malaysia Sharia Stock Index Performance Using Sharpe, Treynor, and Jensen Methods - Azizah, Fauziah; Handayani, Sri Setya; Riskayanto; Rizaldy, Muhamad Rizky (International Journal of Islamic Business and Economics (IJIBEC), 2024)
The research aims to measure the performance of stock indices and analyze the comparative performance of sharia stock indices in Indonesia (JII-70) and Malaysia (FBMS) during and after the COVID-19 pandemic. The performance assessment used was the Sharpe, Treynor, and Jensen method. Sharpe concept will be used to measure the risk premium for each unit of risk in the portfolio, Treynor will be used to measure portfolio performance assuming that the Reward to Volatility Ratio (RVR) of a well-diversified portfolio, and Jensen will measure that estimates a constant rate of return over the investment period. The performance of JII-70 and FBMS will be comparatively analyzed using the independent sample t-test with Eviews-12 software. According to Treynor, the test results show that the performance of the JII-70 stock index is positive. In contrast, according to the Sharpe and Jensen indices, it is negative, while the performance of FBMS based on these three indices shows negative results. The performance of the JII-70 stock index is higher than the FBMS index, although the difference is not significant. Meanwhile, according to the Jensen index, FBMS performance is better than JII-70 performance. It can be concluded that the Jakarta Islamic Index-70 (JII-70) performance is better than the FTSE Bursa Malaysia EMAS Sharia (FBMS). The findings of this study help regulators and practitioners design essential strategies in light of varying stock market dynamics during the pandemic.